Different ways to enhance the permeability, lipophilicity, and bioavailability of the antidiabetic drug, Metformin: Review Article - Salar Masoomzadeh; Maryam Maghsoodi (Shiraz University of Medical Sciences, 2022)
Metformin is a drug that needs improvement in its bioavailability and absorption. This  can be acheived by using different drug delivery systems, making prodrugs, and changing the drug release environment. Drug delivery systems are used for various reasons, for example, targeted drug delivery, protecting the drugs from destruction by enzymes, and enhancing the drug's absorption, permeability, and bioavailability. According to the studies and surveys, the permeability, absorption, and bioavailability of metformin can be improved in many ways, like making prodrugs and using carriers. Prodrugs and lipid-based carriers like nanostructured lipid carriers and lipid-based polymers are the best methods that can help the medical system to reduce the dose of metformin usage in patients and reduce the side effects. Please cite this article as: Salar Masoomzadeh, Maryam Maghsoodi. Different ways to enhance the permeability, lipophilicity, and bioavailability of the antidiabetic drug, Metformin: Review Article. Trends in Pharmaceutical Sciences. 2022;8(2):69-74 .doi: 10.30476/TIPS.2022.93380.1125